Manajemen Stres dalam Program Akselerasi Pendidikan Perspektif Neurosains - Urbaningkrum, Santi Mahmuda; Suyadi, Suyadi; Sulaiman, Muhammad (Jayapangus Press, 2024)
The existence of an accelerated education program is a forum for developing students' potential intelligence and special talents. However, of course, in its implementation there are several weaknesses found, one of which can cause students to experience stress due to unbalanced brain work or pressure that causes emotional or mood disturbances. Stress can be better managed with stress management with the relevance of a neuroscientific perspective. The aim of this research is to find out the acceleration program from a neuroscience perspective and stress management solutions for children who are members of the program. This type of research uses a qualitative method with a literature study approach, which is then analyzed using the content analysis method. The results of this research are that stress resulting from the acceleration program is closely related to the functioning of the brain, namely the limbic brain and neocortex, as well as a decrease in the hormone dopamine. Stress management that can be done is Problem Focused Coping, Emotional Focus Coping, Behavioral approach, and Guilded Imagery. Apart from that, stress management from an Islamic perspective is also effective in reducing stress, such as performing prayers, dhikr, prayers, reading the Koran, taking part in Islamic studies, and also instilling sincere and patient intentions.